“From Sea to Screen”: Government Digital Communication Strategies in Framing Maritime Security in the Riau Islands - Irfan Harmain; Dian Mustika Intan; Dahlan Dahlan; Ria Anisa; Latifah Gusri (LEGAL BRIEF, 2026)
The strategic location of the Riau Islands Province places it at the frontline of Indonesia’s maritime security challenges, particularly in relation to transnational crime and border governance. In the digital era, local governments increasingly rely on digital communication to frame maritime security issues; however, the communicative construction of these narratives remains insufficiently examined. This study aims to analyze how the Riau Islands Provincial Government frames maritime security through digital communication strategies. This research employs a descriptive qualitative approach using Robert N. Entman’s framing analysis. The data of the study comprises official digital communications produced by the Riau Islands Provincial Government, including selected social media posts, official website content, press releases, and policy-related digital materials on maritime security. Primary data were collected through in-depth interviews with representatives from government offices. Secondary data were collected through documentation, digital observation, and content archiving. Data were analyzed using Entman’s four framing dimensions: problem definition, causal interpretation, moral evaluation, and treatment recommendation. The findings reveal that maritime security is predominantly framed as an issue of sovereignty and national identity rather than merely an economic or technical concern. Disruptions to maritime security are constructed through narratives of external transnational threats and internal coastal governance challenges, reinforced by moral values of patriotism and coastal solidarity. Policy solutions emphasize institutional synergy among maritime agencies and maritime legal education for coastal communities. This study concludes that digital communication effectively builds symbolic legitimacy for maritime security policies but remains largely top-down and representational. The findings imply the need for more inclusive and participatory digital governance to strengthen substantive public engagement in maritime security